2019
DOI: 10.21873/invivo.11743
|View full text |Cite
|
Sign up to set email alerts
|

Second-generation Probiotics Producing IL-22 Increase Survival of Mice After Total Body Irradiation

Abstract: Background/Aim: Intestinal damage induced by total body irradiation (TBI) reduces leucine-rich repeatcontaining G-protein-coupled receptor 5 (Lgr5)-expressing stem cells, goblet, and Paneth cells, breaching the epithelial lining, and facilitating bacterial translocation, sepsis, and death. Materials and Methods: Survival was measured after TBI in animals that received wild-type or recombinant bacteria producing interleukin-22 (IL-22). Changes in survival due to microbially delivered IL-22 were measured. Lactob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 40 publications
1
42
2
Order By: Relevance
“…In this study, we demonstrated the proof of concept that engineered L. reuteri can secrete biologically active mIL-22, which reduced markers related to liver disease in a model of diet-induced obesity. We believe that our study, combined with recent studies demonstrating the efficacy of recombinant L. reuteri in animal disease models of total body irradiation and alcohol-induced liver disease (11,18), reveals the potential to develop L. reuteri as a next-generation probiotic to treat disease in the clinic.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In this study, we demonstrated the proof of concept that engineered L. reuteri can secrete biologically active mIL-22, which reduced markers related to liver disease in a model of diet-induced obesity. We believe that our study, combined with recent studies demonstrating the efficacy of recombinant L. reuteri in animal disease models of total body irradiation and alcohol-induced liver disease (11,18), reveals the potential to develop L. reuteri as a next-generation probiotic to treat disease in the clinic.…”
Section: Discussionmentioning
confidence: 75%
“…Alternative approaches may therefore be more efficient. For example, we recently demonstrated that activation of native prophages in L. reuteri can lyse the cell and subsequently release a recombinant mature protein that has accumulated inside the cell; this approach has proven successful in preclinical disease models (11,18). Using bacterial lysis to release mature proteins also has the advantage that lysis can be optimized to contribute to containment.…”
Section: Discussionmentioning
confidence: 99%
“…Second-generation probiotics are also being developed to take advantage of the natural properties of these bacteria, using microbial-mediated delivery of drugs to target the gut. Researchers have engineered probiotics that produce IL-22 ( Zhang et al, 2020 ), a cytokine with anti-inflammatory properties known to stabilize both intestinal Paneth cells and Lgr5+ intestinal stem cells ( Zha et al, 2019 ). In this study, C57BL/6 mice were exposed to 9.25-Gy TBI and then treated with Lactobacillus reuteri –producing IL-22 strains postirradiation via oral gavage.…”
Section: The Effects Of the Microbiome On The Radiation Responsementioning
confidence: 99%
“…A 30% improvement in survival was noted, as compared to animals dosed only with the IL-22 protein. Time of administration of the bacteria was also examined, and a survival advantage could be seen even when dosed at 72-h postirradiation, with the highest benefit seen at 24 h (85%) and 48 h (70%) postirradiation administration ( Zhang et al, 2020 ).…”
Section: The Effects Of the Microbiome On The Radiation Responsementioning
confidence: 99%
“…Some forms of combined injury may elevate or exacerbate the same cellular death pathways involved in irradiation cell killing and necessitate modifying the dose of a radioprotector to be administered. Space radiation protectors and mitigators will likely also include the use of novel orally administered second-generation probiotics and other nutraceuticals [ 124 ].…”
Section: Countermeasuresmentioning
confidence: 99%